Hybrid organic-inorganic perovskites - Li, Wei (Professor of materials science); Stroppa, Alessandro; Wang, Zhe-Ming; Gao, Song (Professor in chemistry and molecular engineering) (Wiley-VCH, 2020)
Hybrid organic-inorganic perovskites (HOIPs) have attracted substantial interest due to their chemical variability, structural diversity and favorable physical properties the past decade. This materials class encompasses other important families such as formates, azides, dicyanamides, cyanides and dicyanometallates. The book summarizes the chemical variability and structural diversity of all known hybrid organic-inorganic perovskites subclasses including halides, azides, formates, dicyanamides, cyanides and dicyanometallates. It also presents a comprehensive account of their intriguing physical properties, including photovoltaic, optoelectronic, dielectric, magnetic, ferroelectric, ferroelastic and multiferroic properties. Moreover, the current challenges and future opportunities in this exciting field are also been discussed. This timely book shows the readers a complete landscape of hybrid organic-inorganic pervoskites and associated multifuctionalities.